Wenn der Vater fehlt: epidemiologische Befunde zur Bedeutung früher Abwesenheit des Vaters für die psychische Gesundheit im späteren Leben - Franz, Matthias; Schmitz, Norbert; Lieberz, Klaus; Schepank, Heinz (Zeitschrift für psychosomatische Medizin und Psychotherapie, 1999)
SummaryFacing the increasing number of single-parent-families we investigated the impact of fathers absence within the first six years of childhood on psychic/psychosomatic impairment in later life. We used data from the Mannheim Cohort Study on the Epidemiology of Psychogenic (neurotic spectrum) Disorders for a comparison of extreme groups with a favourable or bad course of clinical impairment. In adition we performed regression analysis of the long term course of clinical impairment for the total follow-up sample (mean follow-up intervall 11 years, N=301) with psychometric, clinical and childhood variables. The absence of the probands father (> six months within the first six years of life) was a significant independend predictor of clinical impairment in later life, accompanied by clinical and psychometric variables. A significant and increasing impairment existed even in 73 of 125 older probands (birth cohort 1935), who missed their father in early childhood. The sociopolitical implications of these findings are discussed.
Online veröffentlicht: September 2015
Gesehen am 16.11.2020